Research on cost and carbon reduction using the optimization of composite slabs modules based on bim technology - Huo Haie; Liu Mingrong; Zhou Juncen (Scientific Reports)
Abstract As one of the primary precast components in prefabricated construction, composite slabs have increasingly attracted interest for their costs as well as carbon footprint in production and installation stages. Conventional methods for separating composite slabs can lead to a building project necessitating multiple specifications of composite slabs. Due to the requirement to customize molds for different modulus of composite slabs, the production process experiences a substantial rise in energy consumption and resource waste. This not only increases production complexity and expenses but also indirectly raises carbon emissions. This paper conducts secondary development of a plugin based on the Building Information Modeling (BIM) technology platform, C# language and Visual Studio 2017 to optimize the modular design of composite slabs with the help of Revit software. This plugin can quickly and intelligently recommend the most suitable combination of composite slabs specifications based on the actual size of the floor slabs, thereby greatly reducing the types of composite slabs required. The modular optimization process developed in this paper is applied to an actual engineering project, the results show that the types of composite slabs molds after optimization are reduced from 9 to 4, and the mold cost is reduced by 69.60%. At the same time, the carbon emissions of the optimized composite slabs in the production stage are reduced by 7.03% compared with those before optimization. It is observed that this optimization scheme not only significantly reduces the production costs of composite slabs and improves production efficiency but also effectively reduces carbon emissions during the production phase of composite slabs.